THE RELATIONSHIP BETWEEN ORGANIZATIONAL JUSTICE AND JOB INVOLVEMENT ON NURSE'S ORGANIZATIONAL CITIZENSHIP BEHAVIOR (EXAMINING THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT) - Umiriyana, Umiriyana; Cahyono, Luthfi Basith Eko; Armanu, Armanu; Puspaningrum, Astrid (Jurnal Aplikasi Manajemen, 2020)
This study aims to understand the role of organizational commitment in mediating the influence of organizational justice and job involvement on nurses' organizational citizenship behavior. This explanatory research was conducted on the nurses of Universitas Muhammadiyah Malang Hospital (UMM Hospital). From the population of 127 nurses, 96 were selected as the sample through a proportionate random sampling method. The statistical analysis through Structural Equation Modelling found that organizational justice has no significant influence on organizational citizenship behavior, job involvement has a significant influence on organizational citizenship behavior, organizational commitment has a significant influence on organizational citizenship behavior, organizational justice has a significant influence on organizational citizenship behavior through organizational commitment, and job involvement has a significant influence on organizational citizenship behavior through organizational commitment.